An Assessment of Applicability of SNP Chip Developed for Domestic Goats in Genetic Studies of Caucasian Tur (Capra caucasica) - Arsen V. Dotsev; Andrey N. Rodionov; Veronika R. Kharzinova; Sergey N. Petrov; Dmitry G. Medvedev; Vugar A. Bagirov; Gottfried Brem; Natalia A. Zinovieva (Diversity, 2021)
Caucasian tur (Capra caucasica) is native to Greater Caucasus Mountain Chain from Azerbaijan and Georgia in the East to Krasnodar region of Russia in the West. This species is divided into two subspecies (by some authors into species)—East-Caucasian tur and West-Caucasian tur and a subpopulation referred to as Mid-Caucasian tur. Up to date most of the genetic studies of Caucasian tur are based on mitochondrial DNA sequences and comprehensive investigation based on nuclear DNA is required for clarification of its genetic diversity and population structure. In our work, we assessed the applicability of Illumina Goat SNP50 BeadChip for genetic studies of Caucasian tur. Total of 15 specimens of Capra caucasica including East-Caucasian tur from Dagestan (E_TUR, n = 5), West-Caucasian tur from Karachay-Cherkessia (W_TUR, n = 5), and Mid-Caucasian tur from Kabardino-Balkaria (M_TUR, n = 5) were genotyped. After quality control, 5544 polymorphic loci, which were distributed all over 29 autosomes, were detected. The lowest number of SNPs was found on the 25th chromosome—68, and the highest on the 1st chromosome—348. It was shown that all the three groups of Caucasian tur clustered separately. A total of 2061 SNPs were common for all the populations, 594 were found only in W_TUR, 689 in E_TUR, and 530 in M_TUR. Individual heterozygosity ranged from 0.273 to 0.282 in W_TUR, from 0.217 to 0.253 in E_TUR, and from 0.255 to 0.283 in M_TUR. A clinal pattern of genetic variation was revealed. It was suggested to consider Caucasian tur a single species with several ecotypes. Thus, in our study we demonstrated that the Illumina Goat SNP50 BeadChip developed for domestic goats can be used as a useful tool for genetic studies of Caucasian tur.